2017
DOI: 10.1111/josh.12488
|View full text |Cite
|
Sign up to set email alerts
|

Investigating How to Align Schools' Marketing Environments With Federal Standards for Competitive Foods

Abstract: Low monetary resources were required to remove marketing not compliant with federal nutrition standards for foods sold in schools. Several key challenges remain to sustain efforts. This study provides timely information for policymakers to support crafting policies that address the realities of school nutrition environments and universal enforcement challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…FBM has been shown to influence children's preferences and dietary intake 118,119 and is commonly found in schools. 120 The 1 study in this systematic review that addressed FBM found a decrease in the number of instances that FBM did not align with nutrition standards, and that removing or replacing noncompliant marketing was not resource intensive 108 ; however, schools may need technical assistance to identify marketing that does not align with federal nutrition standards. Schools can address FBM in a variety of ways, including leveraging wellness policies to limit or exclude certain FBM content and providing education to students and staff about how to identify deceitful marketing practices.…”
Section: Interventions To Improve the School Nutrition Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…FBM has been shown to influence children's preferences and dietary intake 118,119 and is commonly found in schools. 120 The 1 study in this systematic review that addressed FBM found a decrease in the number of instances that FBM did not align with nutrition standards, and that removing or replacing noncompliant marketing was not resource intensive 108 ; however, schools may need technical assistance to identify marketing that does not align with federal nutrition standards. Schools can address FBM in a variety of ways, including leveraging wellness policies to limit or exclude certain FBM content and providing education to students and staff about how to identify deceitful marketing practices.…”
Section: Interventions To Improve the School Nutrition Environmentmentioning
confidence: 99%
“…32 Food and beverage marketing. One study reported on schools' efforts to assess whether FBM practices in schools 108 were compliant with federal regulations for local school wellness policies 8 and on their efforts to improve the school nutrition environment and decrease the number of noncompliant instances of FBM. Through the process of assessing current practices and providing technical assistance on replacing marketing that was not compliant, schools were able to improve the school nutrition environment and decrease the number of noncompliant instances of FBM.…”
Section: Interventions To Improve the School Nutrition Environmentmentioning
confidence: 99%
“…Demand‐side interventions, such as nutrition education and modifications to the cafeteria environment and layout, can influence students' KAP and receptivity to choosing and eating healthier options. Only 1 study evaluated the impact of nutrition standards for foods marketed in schools and technical assistance to support their adoption, highlighting the need for more evaluations of this marketing strategy 31 . Supply‐side interventions influence how food is served, such as providing ongoing professional development for school nutrition staff, improving the palatability of school meals, offering taste tests, pre‐slicing fruit, providing recess before lunch, and offering incentives or rewards for trying healthier options, can increase students' selection and consumption of healthier items 18…”
Section: Evidence‐based Strategiesmentioning
confidence: 99%